2020
DOI: 10.1002/tesq.570
|View full text |Cite
|
Sign up to set email alerts
|

Toward Biliteracy: Unpacking the Contribution of Mid‐adolescent Dual Language Learners’ Spanish and English Academic Language Skills to English Reading Comprehension

Abstract: Academic language skills support mid‐adolescents’ comprehension of the language of school texts. To date, scarce research has explored associations between dual academic language skills and reading comprehension among mid‐adolescent dual language immersion (DLI) students. This study examined individual differences in Spanish and English academic language skills and their contribution to English reading comprehension in a cross‐sectional sample of DLI students in Grades 4–6 (N = 101). Taking advantage of a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In a climate of increasing interest in DLI programs, we aimed to better understand the links between DLI learners’ Spanish and English ALs skills, and their contribution to English reading comprehension (as measured by a statewide ELA assessment) for upper elementary students (Grades 4 and 5). Rather than focus on the relations between language skills broadly acquired across contexts, we focused on a circumscribed set of co-occurring school-relevant language skills, or CALS, shown in prior research to support reading comprehension within languages (in English and Spanish), but only minimally investigated cross-linguistically in DLI students (Aguilar et al, 2019). We drew on Cummins’s LIH, but with an understanding of cross-linguistic connections as reciprocal because we studied learners developing two languages simultaneously in school contexts where Spanish-English biliteracy is fostered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a climate of increasing interest in DLI programs, we aimed to better understand the links between DLI learners’ Spanish and English ALs skills, and their contribution to English reading comprehension (as measured by a statewide ELA assessment) for upper elementary students (Grades 4 and 5). Rather than focus on the relations between language skills broadly acquired across contexts, we focused on a circumscribed set of co-occurring school-relevant language skills, or CALS, shown in prior research to support reading comprehension within languages (in English and Spanish), but only minimally investigated cross-linguistically in DLI students (Aguilar et al, 2019). We drew on Cummins’s LIH, but with an understanding of cross-linguistic connections as reciprocal because we studied learners developing two languages simultaneously in school contexts where Spanish-English biliteracy is fostered.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors that may contribute to reading development in DLI settings—where students use two languages for reading, writing, and learning—are increased opportunities to learn academic language resources (Aguilar, Uccelli, & Phillips Galloway, 2019). Academic languages (ALs) encompass lexical, syntactic, and discursive resources used recurrently for explaining concepts in the disciplines, exploring and negotiating understandings in academic communities, and for flexibly enacting social roles and stances prevalent in these communities (e.g., epistemically cautious expert, skeptical colleague, or respectful critic).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntactic features prevalent in school texts, such as elaborated noun phrases, lengthy relative clauses, conceptual anaphora, and the use of distinctive connectives, have been found to pose particular challenges for written text comprehension (Scott and Balthazar, 2010;Uccelli et al, 2015a) in students generally and in L2 learners more specifically (Phillips Galloway and Uccelli, 2019). Crosslinguistically, L2 English academic skills and reading comprehension have been found to be positively associated with L1 Spanish academic vocabulary (Lubliner and Hiebert, 2011) and with academic language skills broadly measured as combined lexical, syntactic, and discourse skills (Aguilar et al, 2020;Phillips Galloway and Uccelli, 2019). However, how L2 learners process distinctive syntactic features of written school texts is not well understood, and little prior research has examined L2 syntactic processing beyond morphosyntax in written academic discourse comprehension.…”
Section: The Current Studymentioning
confidence: 99%
“…Studies of multilingual students educated in English‐only U.S. classrooms have revealed a similar pattern: CALS contribute significant variance to students’ text understanding (Phillips Galloway & Uccelli, 2019). Studies of learners educated in U.S. dual‐language Spanish–English school settings have further found that CALS measured in both Spanish and English contribute unique variance to students’ English text comprehension (Aguilar, Uccelli, & Phillips Galloway, 2020; Phillips Galloway, Uccelli, Aguilar, & Barr, 2020). Linked with the idea that stores of language knowledge are interdependent, these studies indicated that both Spanish and English CALS are positively related, yet each also contribute uniquely to explain the variability in dual‐language learners’ English reading comprehension.…”
Section: Readers’ Academic Language Skills and Social Practices: Three Key Understandingsmentioning
confidence: 99%